The Use of Augmented Reality Flashcard in Enriching Students’ vocabulary - Nursabra Nursabra; Syamsinar Syamsinar; Nur Fadillah Nurchalis; Rizka Nuralima (Universitas Cokroaminoto Palopo, 2023)
The objective of the research is to find out whether or not the Augmented Reality Flashcard can enrich the young learners’ vocabulary. This study is a pre-experimental study with a population of RA. Perwanida 1 Lipu for the 2020/2021 academic year, with a total population of 64 young learners. The sample of this study was group 1 from class B RA Perwanida 1 Lipu, consists of 22 young learners. The instrument used in this study was a vocabulary test. The researcher was giving a pre-test and post-test in the form of an objective test, namely multiple choice. This research used descriptive statistics to analyze the data. Descriptive statistics used in this research include summation, average, standard deviation, and frequency table. The results of this study indicate that the use of Augmented Reality teaching media has a positive impact on enriching students' vocabulary. It was proven from the increase in student scores from the pre-test to the post- test with the average value during the pre-test was 3.02 and the average value after the post-test was 6.02. So, it can be concluded that Augmented Reality flashcard media has an effect in increasing the students' vocabulary.